2009
DOI: 10.1097/01.aids.0000363776.76129.fd
|View full text |Cite
|
Sign up to set email alerts
|

Fertility desires and infection with the HIV: results from a survey in rural Uganda

Abstract: HIV-positive individuals in the Kabarole region have a much greater desire to stop childbearing than their HIV-negative counterparts. The barriers to utilizing family planning services, as evidenced through the very low use of highly effective contraceptive methods, have to be jointly addressed by HIV/AIDS care/prevention and family planning programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 25 publications
(40 reference statements)
6
66
3
Order By: Relevance
“…6 The HIV epidemic is having a profound and complex effect on reproductive behavior in Africa. A desire for fewer children among HIV-positive women than among HIV-negative women or women of unknown status has been documented both in cross-sectional studies [7][8][9][10][11][12] and in longitudinal studies that followed women after they received their HIV diagnosis. [13][14][15][16] Women's decreased desire for additional children after learning they are HIVpositive has been explained by concerns over motherto-child transmission and leaving orphans, as well as by perceived health risks involved in pregnancy for an HIVpositive woman.…”
mentioning
confidence: 99%
“…6 The HIV epidemic is having a profound and complex effect on reproductive behavior in Africa. A desire for fewer children among HIV-positive women than among HIV-negative women or women of unknown status has been documented both in cross-sectional studies [7][8][9][10][11][12] and in longitudinal studies that followed women after they received their HIV diagnosis. [13][14][15][16] Women's decreased desire for additional children after learning they are HIVpositive has been explained by concerns over motherto-child transmission and leaving orphans, as well as by perceived health risks involved in pregnancy for an HIVpositive woman.…”
mentioning
confidence: 99%
“…LNG: Levonorgestrel-Releasing Intrauterine System (Mirena®), ENG: Etonogestrel Implant (Nexplanon or Implanon®), DMPA: Depot Medroxyprogesterone Acetate COC combined oral contraceptive, Patch (Ortho Evra®), Ring (Nuva Ring®) Condoms were the primary contraceptive; persons who used condoms for dual protection are listed according to the hormonal contraceptive utilized. [4,10,11,[17][18][19][20]. Tassiopoulos noted that 28% of perinatally infected adolescents 10 to 18 years of age (males and females) reported sexual intercourse, 62% had recent intercourse without a condom, and the median age of sexual debut was 14 years of age [20].…”
Section: Discussionmentioning
confidence: 99%
“…HIV infected adolescents reported prior use of dual protection during 16% of their visits [4]. Previous international studies have demonstrated that HIV positive adolescent and adult women are more likely to request injectable contraceptives than their HIV negative peers [4,9,[11][12][13]. Risk of HIV acquisition or progression among hormonal contraception users has been a recent concern based on international trials [14].…”
Section: Introductionmentioning
confidence: 99%
“…This study also indicated that there is no association between the women's annual income and their desire to have children in future and this is consistent with the finding of the other study conducted in Canada (Loutfy et al, 2009). However, a study conducted in one developing country, Uganda revealed differences between annual income and fertility desire of PLWH (Heys, Kipp, Jhangri, Alibhai & Rubaale, 2009). Although, this study showed no relationship, it is an expected fact that people living with HIV who have higher education and high income level have more desire to have children (Alemayehu, & Aregay 2012;Heard et al, 2007;Heys et al, 2009;Wekesa & Coast, 2014).…”
Section: Phase I (Structural Survey)mentioning
confidence: 99%
“…However, a study conducted in one developing country, Uganda revealed differences between annual income and fertility desire of PLWH (Heys, Kipp, Jhangri, Alibhai & Rubaale, 2009). Although, this study showed no relationship, it is an expected fact that people living with HIV who have higher education and high income level have more desire to have children (Alemayehu, & Aregay 2012;Heard et al, 2007;Heys et al, 2009;Wekesa & Coast, 2014). All the participants of this study were on government assistance and not highly educated.…”
Section: Phase I (Structural Survey)mentioning
confidence: 99%